Intangible Marketing: The servicescape and the use of physical evidence projection of service environments - Schuster, Marcelo da Silva (2016)
Considering the numerous influences in consumer perceptions, existing in the service environment, this study aimed to create a framework on use of servicescape. Has been analyzed scales used, variables, dimensions, environments and constructs used in previous publications. The chosen methodology was bibliometrics, using the Scopus database. Of the 85 selected articles, 36 used some kind of servicescape scale. These were analyzed manually and individually by content analysis. Most studies conducted research with consumers and the most used environment was hospitality (malls, restaurants, hotels). The resulting framework reflects the plurality of variables, factors and constructs linked to a discussion about service environment on consumer studies. This study contributes literature on the subject, but mainly for the construction of appropriate metric and future empirical studies.